A Brief Study on Potentiality of Fruit and Vegetable Waste by Anaerobic Co-digestion with Municipal Sewage Sludge and Biogas Yield - Anhuradha, S.; Arrrivukkarasan, S. (Recent Trends in Chemical and Material Sciences Vol. 3, 2021)
The co-digestion technique, which uses anaerobic digestion to treat two or more organic biodegradable waste streams, has a lot of potential for proper solid waste disposal. Under mesophilic conditions, the anaerobic co-digestion of fruit and vegetable waste (FVW) and municipal sewage sludge (MSS) was explored and compared to separate digestion of the substrates. The continuous studies were performed at an organic loading rate of 1.5 g VS/l.day and at an HRT of 20 days. It was observed that FVW had better performance than the MSS. However, FVW addition led to improvement of the process stability, with low Volatile Fatty Acids (VFA) / Total Alkalinity (TA) ratio and improves the gas production yield with its co-substrates. Specific gas production values of three reactors were: (i) 0.49 l/g VSin & 1.0 l/g VSdes for FVW, (ii) 0.261 l/g VSin & 0.643 l/g VSdes for MSS and (iii) 0.613 l/g VSin & 1.078 l/g VSdes for co- digestion of FVW and MSS. Co-digestion is proven to produce more biogas. Anaerobic co-digestion of FVW and MSS performed better in terms of gas production, reactor stability in co-digestion substrates and buffering capacity. It is concluded that anaerobic co-digestion of MSS and FVW is an attractive method for environmental protection and energy savings.